Optimizing the patient positioning workflow of patients with pelvis, limb, and chest/spine tumors at an Ion-Beam Gantry based on optical surface guidance - Qubala, Abdallah; Schwahofer, Andrea; Jersemann, Stefan; Eskandarian, Saleh; Harrabi, Semi B.; Naumann, Patrick; Winter, Marcus; Ellerbrock, Malte; Shafee, Jehad; Abtehi, Samira; Herfarth, Klaus; Debus, Jürgen; et al. (Advances in radiation oncology, 2023)
Purpose - Surface-guided radiation therapy (SGRT) has been investigated intensively to ensure correct patient positioning during a radiation therapy course. Although the implementation is well defined for photon-beam facilities, only a few analyses have been published for ion-beam therapy centers. To investigate the accuracy, reliability, and efficiency of SGRT used in ion-beam treatments against the conventional skin marks, a retrospective study of a unique SGRT installation in an ion gantry treatment room was conducted, where the environment is quite different to conventional radiation therapy. - Methods and Materials - There were 32 patients, divided into 3 cohorts—pelvis, limb, and chest/spine tumors—and treated with ion-beams. Two patient positioning workflows based on 300 fractions were compared: workflow with skin marks and workflow with SGRT. Position verification was followed by planar kilo voltage imaging. After image matching, 6 degrees of freedom corrections were recorded to assess interfraction positioning errors. In addition, the time required for patient positioning, image matching, and the number of repeated kilo voltage imaging also were gathered. - Results - SGRT decreased the translational magnitude shifts significantly (P < .05) by 0.5 ± 1.4 mm for pelvis and 1.9 ± 0.5 mm for limb, whereas for chest/spine, it increased by 0.7 ± 0.3 mm. Rotational corrections were predominantly lowered with SGRT for all cohorts with significant differences in pitch for pelvis (P = .002) and chest/spine (P = .009). The patient positioning time decreased by 18%, 9%, and 15% for pelvis, limb, and chest/spine, respectively, compared with skin marks. By using SGRT, 53% of all studied patients had faster positioning time, and 87.5% had faster matching time. Repositioning and consequent reimaging decreased from about 7% to 2% with a statistically significant difference of .042. - Conclusions - The quality of patient positioning before ion-beam treatments has been optimized by using SGRT without additional imaging dose. SGRT clearly reduced inefficiencies in the patient positioning workflow.
Gesehen am 23.10.2023